PENGARUH PRODUK DAN HARGA SOUVENIR TERHADAP KEPUASAN WISATAWAN DI LAPAU PANJANG CIMPAGO KOTA PADANG - Kurniawan, Teddy; Yuliana, Yuliana; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of research is to determine the Effects of Products and Prices Souvenirs Against Satisfaction Tourists in Lapau Panjang Cimpago Padang City. This type of research is a causal associative research. Population in the research is not known the exact number. Sampling technique is non probability sampling, using accidental sampling. Number of sample in this research amounted to 97 people. Data collection using a questionnaire based with the Likert scale that tested for validity and reliability. Based on the results of research using using multiple linear regression shows that the product and price influence the satisfaction of tourists as a dependent variable significantly with the value of R square of 0.344.Key Words : Product, Price. Satisfaction, Tourist, Souvenir1 Prodi